(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to reveal the most important challenges facing the acceptance of children with autism spectrum disorder in schools. To achieve this goal, the researchers prepared a questionnaire consisting of (18) sub-questions. The researchers then applied the questionnaire to the research sample, which amounted to (187), consisting of (106) teachers, (42) supervisors, and (39) school principals. They were selected using a simple random method. Several results emerged, the most prominent of which are: The results showed that a small percentage of participants strongly believed that current legislation provides sufficient support for children with autism spectrum disorder to enroll in school. This indicates that some schools may have succeeded in effectively implementing these laws, which has positively impacted the evaluation of this group of educators. Participants’ responses, at a high rate, reflected a broad consensus that current laws and regulations are insufficient and require substantial amendments. 3- The research results also indicated that curricula can be somewhat partial and do not meet all the needs of children with autism spectrum disorder. Some materials or interactions can be adapted, but curricula generally do not take into account the wide diversity of children’s basic needs. In light of this, a number of recommendations and proposals related to the research topic were reached.